INrich, Rapid and Robust Method to Enrich N-Terminal Proteome in a Highly Multiplexed Platform - Ju, Shinyeong; Kwon, Yumi; Kim, Jeong Mok; Park, Daechan; Lee, Seonjeong; Lee, Jin Won; Hwang, Cheol Sang; Lee, Cheolju (Analytical Chemistry, 2020)
The field of terminal proteomics is limited in that it is optimized for large-scale analysis via multistep processes involving liquid chromatography. Here, we present an integrated N-terminal peptide enrichment method (iNrich) that can handle as little as 25 μg of cell lysate via a single-stage encapsulated solid-phase extraction column. iNrich enables simple, rapid, and reproducible sample processing, treatment of a wide range of protein amounts (25 μg ∼1 mg), multiplexed parallel sample preparation, and in-stage sample prefractionation using a mixed-anion-exchange filter. We identified ∼5000 N-terminal peptides (Nt-peptides) from only 100 μg of human cell lysate including Nt-formyl peptides. Multiplexed sample preparation facilitated quantitative and robust enrichment of N-terminome with dozens of samples simultaneously. We further developed the method to incorporate isobaric tags such as a tandem mass tag (TMT) and used it to discover novel peptides during ER stress analysis. The iNrich facilitated high-throughput N-terminomics and degradomics at a low cost using commercially available reagents and apparatus, without requiring arduous procedures.
Keywords: High throughput; Large-scale analysis; Multistep process; Parallel samples; Prefractionation; Sample preparation; Sample processing; Solid-phase extraction columns